Visual-Spatial Ability in Solving Geometry Problems Viewed from Gender Using the Flipped Classroom Model - Laila Rahmawati; Yeni Wulandari (IAHN-TP Palangka Raya, 2022)
Visual-spatial ability is the ability to understand the perspective of space and dimensions. Good visual-spatial skills will make it easier to learn spatial geometry because it is easy to remember images and has a strong imagination. One of the visual-spatial abilities is influenced by gender factors. So in this case the ability of a person, especially a prospective elementary school teacher, must be able to have good special visual abilities. This study uses a descriptive method with a qualitative approach. This study aims to describe the visual-spatial intelligence of students in understanding spatial structures viewed from gender using the flipped classroom model. The researcher himself as the main instrument of the study, while the supporting instruments are in the form of tests of visual-spatial abilities and interview guidelines. The results of this study indicated that visual-spatial intelligence that is assumed to be owned more by men than by women is not necessarily true, because the intelligence of each person is not only seen from their gender but also their ability to understand spatial or visual patterns they have. Therefore, in the future teachers or lecturers are expected to frequently train students' spatial intelligence in their classes so that students will be able to visualize images and translate images in their minds.